A mixed-methods study on the impact of experiential financial education on Chinese students’ financial literacy and wellbeing - Zhou, Yani; Hussin, Muhammad; Abd Majid, Mohamad Zuber (Institute of Advanced Engineering and Science, 2025)
This study examines the impact of experiential financial education on financial literacy and wellbeing among Chinese university students. In response to the growing demand for practical financial skills in China, where traditional financial education often focuses on theory, a mixed-methods approach with a sequential explanatory design was used. The quantitative phase employed a quasi-experimental method, involving an experimental group (EG) receiving experiential education and a control group (CG) following traditional methods, each with 60 students recruited through purposive sampling. Data on financial literacy and wellbeing were collected via pre- and post-intervention questionnaires. To gain deeper insights, qualitative interviews were conducted with nine students using voluntary sampling. The quantitative results showed that the EG significantly outperformed the CG in financial literacy (knowledge, behavior, and attitude) and financial wellbeing (security, resilience, control, and freedom of choice). Qualitative findings reinforced these results, revealing themes such as the practical application of financial knowledge, increased confidence, higher engagement, and the relevance of lessons to real-world financial challenges. Overall, the study underscores the importance of incorporating experiential learning into financial education to boost literacy and wellbeing, providing valuable insights for regions where practical financial education is still evolving.